A new species of the highly modified genus Pseudocerocoma Pic, 1919 from Colombia (Coleoptera: Cantharidae: Ichthyurini) - Serna-Muñoz, Sebastian; Alzate-Cano, Julian David (Zootaxa, 2024)
The genus Pseudocerocoma Pic, 1919 (Coleoptera: Cantharidae: Ichthyurini) was previously recognized as a monotypic genus. Based on material from Antioquia, Colombia, we describe and illustrate Pseudocerocoma tulenapa sp. nov. It differs from the other known species of the genus in the shape of the antennae and the abdominal segment 8, as well as in some aspects of coloration. This new species provides additional evidence for the position of Pseudocerocoma Pic, 1919 as a separate genus from Malthoichthyurus Pic, 1919, also represents the first record of the tribe Ichthyurini in Colombia and shows the importance of the conservation actions carried out in the only known locality, the Tulenapa Biological Station of the Universidad de Antioquia.